98.4k views
2 votes
-2b+2(b-10)=2(10+5b)

User Jasal
by
4.1k points

1 Answer

1 vote

Answer:

b= -4

Explanation:

On both sides of the equation has distributive property. We need to solve that first. Let's start with the left side of the equation.

*Positive multiplied by a negative equals a negative

-2b+2(b-10)= 2(10+5b)

-2b+2b-20= 2(10+5b)

-20= 2(10+5b)

Now let's solve the right side of the equation

-20= 20+10b

-20 -20

-40 = 10b

-40/10 = 10b/10

b= -4

Hope this helps!

User Thamindu DJ
by
4.8k points